Student Perceptions of Character Education Policies in Higher Education at Universitas Negeri Makassar - Sakkir, Geminastiti; Jayadi, Karta (PT ARRUS Intelektual Indonesia, 2024)
This study explores the perceptions of first-semester students in the Fine Arts Education Study Program at Universitas Negeri Makassar regarding character education policies in higher education. Using a qualitative descriptive approach, data were collected from 44 respondents through interviews, observation, and documentation. The findings reveal diverse understandings of character education policies, with students identifying their objectives as fostering integrity, responsibility, and ethical values. Respondents emphasized the integration of character education into the curriculum, teaching methods, and student evaluations. Specific implementations include discussions, case studies, and personal reflections that align with academic and character-building goals. Students largely perceived these values as relevant to academic and social life, fostering discipline, empathy, and collaboration. This research underscores the importance of aligning character education policies with practical applications in teaching and learning processes to cultivate holistic and ethical individuals.